The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1089/gtmb.2016.0186
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study for the Detection of Mutations in the Beta-Globin Gene Among Patients with Hemoglobinopathies in the Bengali Population

Abstract: The present study is the first attempt to screen for β-thalassemia-causing mutations by direct sequencing in different districts of West Bengal. The information obtained from the present study may be helpful for thalassemia management and prenatal mutation detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Among them, CD53 (-T), CD37 (A>G) and −90 (C>T) mutations were first revealed in Fujian province of Southeast China. Moreover, the CD3 (T>C) synonymous mutation had been reported in the Japanese population23 and was first found in the Chinese population. In light of this study, we should pay more attention to the thalassemia gene testing results when it inconsistent with the results of the thalassaemia screening.…”
Section: Discussionmentioning
confidence: 98%
“…Among them, CD53 (-T), CD37 (A>G) and −90 (C>T) mutations were first revealed in Fujian province of Southeast China. Moreover, the CD3 (T>C) synonymous mutation had been reported in the Japanese population23 and was first found in the Chinese population. In light of this study, we should pay more attention to the thalassemia gene testing results when it inconsistent with the results of the thalassaemia screening.…”
Section: Discussionmentioning
confidence: 98%
“…There are a few recent reports of novel mutations as well like Codon 2 (−A), −42 (C>G), and −223 (T>C) from eastern India and Codon 53 (C>T) from West Bengal . We identified 49 different mutations which also included some novel and very rare ones.…”
Section: Discussionmentioning
confidence: 90%
“…33 There are a few recent reports of novel mutations as well like Codon 2 (−A), −42 (C>G), and −223 (T>C) from eastern India 35 and Codon 53 (C>T) from West Bengal. 36 We identified 49 different mutations which also included some novel and very rare ones. and eight of them had a β gene defect [IVS I-5 (G>C)-3, 619 bp deletion-2, codon 41/42-1, Capsite + 1 (A>C)-2].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral-blood lymphocytes via standard phenol-chloroform extraction. The genotypes of the enrolled patients were confirmed using Sanger sequencing (Panja et al, 2017). The resultant chromatograms were analyzed using Chromas Lite (version 2.1) software to screen for mutations.…”
Section: Methodsmentioning
confidence: 99%
“…HbE/β-thalassemia constitutes the majority of all severe β-thalassemia cases worldwide (Hossain et al, 2017), with the highest frequencies observed in India, Bangladesh, Indonesia, Malaysia, Southern China, and Thailand (Noor et al, 2020). Further, it is prevalent in north-eastern states (3- >50%) and in eastern India (3– 4%) (Mohanty et al, 2013; Panja et al, 2017; Algiraigri and Kassam, 2017). HbE/β-thalassemia results from co-inheritance of the mutant β-thalassemia allele from one parent and HbE (CD26, G>A; GAC→AAG, Glu→Lys) from the other.…”
Section: Introductionmentioning
confidence: 99%